Криминальные каникулы: повесть / Е. Н. Вильмонт - Вильмонт Екатерина Николаевна (Детектив + Love, 2010)
Экземпляры: ф.8 (2010) / Инвентарный номер: 53177 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: В 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44